The Effectiveness of Indonesia Supreme Court Regulation Number 1 Year 2016 Concerning Mediation of Marriage Disputes - Sukaenah Sukaenah; Rusli Rusli; M. Taufan B (State Institute for Islamic Studies Palu, 2020)
This paper discusses the effectiveness of Indonesia Supreme Court Regulation No. 1 year 2016 concerning mediation marital disputes in the Religious Court. This study used qualitative research method. Data was gathered through observation, in-depth interviews, and documenta studies. Data were analyzed through data reduction, presentation, verification, and conclusion drawing. The results of the study shows that effectiveness of PERMA No. 1 of 2016 has been successfully implemented, but the regulation is not effective to reduce divorce rates. This is because the cases that have been reconciled are still few compared to failed mediation. The efforts carried out by the mediator to make mediation effective are merely to act as facilitators by explaining the purpose of mediation to litigants, providing facilities to carry out mediation and increasing the ability of mediators. Supporting factors: Implementation of Mediation based on PERMA Number 1 Year 2016 which is effective, Qualification of Mediators, Facilities, Community Compliance and cultural factors. Inhibiting factors includes technical factors such as mediator limitations, longer mediation time, non-technical factors includes lack of understanding for the parties about the importance of mediation.